Inspiratory Muscle Rehabilitation Training in Pediatrics: What Is the Evidence? - Dharini M. Bhammar; Harrison N. Jones; Jason E. Lang (Canadian Respiratory Journal)
Pulmonary rehabilitation is typically used for reducing respiratory symptoms and improving fitness and quality of life for patients with chronic lung disease. However, it is rarely prescribed and may be underused in pediatric conditions. Pulmonary rehabilitation can include inspiratory muscle training that improves the strength and endurance of the respiratory muscles. The purpose of this narrative review is to summarize the current literature related to inspiratory muscle rehabilitation training (IMRT) in healthy and diseased pediatric populations. This review highlights the different methods of IMRT and their effects on respiratory musculature in children. Available literature demonstrates that IMRT can improve respiratory muscle strength and endurance, perceived dyspnea and exertion, maximum voluntary ventilation, and exercise performance in the pediatric population. These mechanistic changes help explain improvements in symptomology and clinical outcomes with IMRT and highlight our evolving understanding of the role of IMRT in pediatric patients. There remains considerable heterogeneity in the literature related to the type of training utilized, training protocols, duration of the training, use of control versus placebo, and reported outcome measures. There is a need to test and refine different IMRT protocols, conduct larger randomized controlled trials, and include patient-centered clinical outcomes to help improve the evidence base and support the use of IMRT in patient care.